Assessment of the role of manipulation under anaesthesia in knee stiffness following total knee arthroplasty - Rajput, Rakesh; Pal, Kunal Kanti; Kumar, Debangshu (International Journal of Research in Orthopaedics, 2025)
About 3-4% of all total knee arthroplasty (TKA) patients develop unfortunately develop stiff knee. There is inadequate understanding of risk factors and a lack of consensus regarding its management protocol. This study aims to assess the risk factors and outcome of manipulation under anaesthesia to treat stiff knee following TKA. 18 knees with stiffness following primary TKA were enrolled in this study who underwent manipulation under anesthesia (MUA) between January 2023 and April 2024. Patient demographics, type of surgery (conventional or robotic), contributing factors and knee motion before and after manipulation were assessed from hospital records. Final FFD and arc of motion was recorded in a follow-up clinic. Female patients were significantly more affected than male. Delayed physiotherapy due to comorbidities was associated with stiffness. 72.22% stiff knee patients had conventional surgery while rest had robotic assisted surgery. Manipulation under anaesthesia led to mean 31.11degree improvement in arc of motion immediate post manipulation and 26.39 degree in final follow-up. There was no complication during MUA. MUA is safe, effective and noninvasive and can be considered as a first line treatment for stiff knee following TKA.